Multimodal synergisms in host stimuli drive landing response in malaria mosquitoes - Manuela Carnaghi (Nature Portfolio, 2021)
Abstract Anopheles mosquitoes transmit malaria, which affects one-fifth of the world population. A comprehensive understanding of mosquito behaviour is essential for the development of novel tools for vector control and surveillance. Despite abundant research on mosquito behaviour, little is known on the stimuli that drive malaria vectors during the landing phase of host-seeking. Using behavioural assays with a multimodal step approach we quantified both the individual and the combined effect of three host-associated stimuli in eliciting landing in Anopheles coluzzii females. We demonstrated that visual, olfactory and thermal sensory stimuli interact synergistically to increase the landing response. Furthermore, if considering only the final outcome (i.e. landing response), our insect model can bypass the absence of either a thermal or a visual stimulus, provided that at least one of these is presented simultaneously with the olfactory stimuli, suggesting that landing is the result of a flexible but accurate stimuli integration. These results have important implications for the development of mosquito control and surveillance tools.